Trauma Exposure and Suicidality in a Pediatric Emergency Psychiatric Population. Issue 2 (February 2022) - Marr, Mollie C.; Gerson, Ruth; Lee, Mia; Storfer-Isser, Amy; Horwitz, Sarah M.; Havens, Jennifer F.
Abstract : Objectives: The increasing rates of depression and suicidality in children and adolescents are reflected in the increasing number of mental health–related visits to emergency departments. Despite the high rates of traumatic exposure experienced by high-acuity children and adolescents and a known link to suicidal ideation, the systematic review of trauma history is not a consistent part of emergency department assessments for suicide ideation or attempt. In the present study, we examined the prevalence of suicidality as well as traumatic exposures in children and adolescents presenting to a dedicated pediatric psychiatric emergency department. Methods: Suicide ideation, suicide attempts, and trauma exposure history were identified through a retrospective chart review of youth (n = 861) who presented to a dedicated child psychiatric emergency department during a 1-year period. Bivariate analyses comparing demographic and trauma history for children with and without suicidality and a multivariable logistic regression were performed. Results: Childhood adversity was common, with 52% of youth reporting at least one type of trauma exposure. Emotional abuse, physical abuse, and sexual abuse/assault were associated with suicidality. Any trauma exposure and the total number of different trauma exposures were associated with reported suicide attempt. After adjusting for sociodemographic characteristics, children who reported a history of emotional abuse had 3.2-fold increased odds of attempted suicide. Children who reported a history of being a victim of bullying had 1.9-fold increased odds of current suicidal ideation. Conclusions: Traumatic experiences were common in youth presenting with suicidality. Traumatic experiences are frequently underrecognized in treatment settings because they are not part of routine evaluations and are often overlooked when trauma-related symptoms are not the presenting problem. Addressing traumatic experiences underlying depression and suicidal ideation is a necessary step in effective treatment. Emergency departments need to implement routine screening for traumatic exposures in children presenting with suicidal ideation or attempt.